Gratitude to God - Dunnington, Kent (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume gathers papers from the fields of philosophy, theology, and empirical psychology on the topic of gratitude to God. Central themes include the difference between gratitude to God and gratitude to human benefactors and correlations between gratitude to God and important life outcomes.